Adaptation and conformity-immigrant parent’s feelings about parenting in Norway: how do immigrant mothers experience parenting in relation to their perception of a Norwegian standard of parenting? - Jones, Marshalee (2015)
The main aim of this study was to discover how immigrant mothers experience parenting in relation to their perception of a Norwegian standard of ‘doing parenting’. Taking the point of departure from an ethnic plural sample group, the study evoked an understanding of a culturally embedded parent and similar challenges faced in adapting to the Westernized ideal of parenting according to modern Norwegian values. Three research questions formed the skeletal frame around which the study would be structured. These questions sought to excavate the parents’ understanding of a Nordic socialized childhood, a reflection on their acculturation process and a consideration as to how the Norwegian society promoted or discouraged parenting practices influenced by their respective cultural contexts. The research was undertaken qualitatively with semi-structured interviews facilitating the data collection process. The sample group consisted of eight mothers, two each from Somalia, Tunisia, Poland and Nigeria who are currently residing in the Rogaland Kommune, Stavanger. A thematic narrative methodological hybrid was exploited as means of designing the data analytic tool. Employing foundational principles of the ‘negotiation culture’, individualistic/collectivistic and acculturation paradigms, a conceptual frame was developed to inform the interpretation of the main findings. The results of the study indicate that the intercultural contact between immigrants and the Norwegian society is one laced with difficulties and ambiguities. The study has proven that irrespective of ethnic, religious or cultural differences, some elements of immigrant parenting are experienced similarly across minority groups; namely cultural shedding, specific child-rearing values, a need for the maintenance of cultural identity, intergenerational conflicts and sociocultural adaptation. The study has also indicated that there exists an intensively ambivalent relationship between the general immigrant population and the Barnevernet (CWS). The findings justified that this reality speaks to unawareness of the disparity between child protection versus child welfare on the part of the migrant community, while unawareness of cultural differences on the institution’s part. The study concludes that cultural sensitivity is an easy phrase to pronounce, but one that presents a paradoxical challenge in defining ‘the best interest’ for children who are at the heart of the policies programs centered on parenting. Migrant parents might be of the view that parenting ought to be a personal matter. However, Norwegian path-dependent values of egalitarianism, ‘sameness’ and the pervasiveness of the CRC on issues of child development, challenges the ability of child protection stakeholders to negotiation a position of mutual understanding.